Policy vs. practice in sport and climate change: the perspectives of key actors in global sport and international development - Ali, Adam Ehsan; Millington, Rob; Darnell, Simon; Smith, Tavis (Frontiers in Sports and Active Living, 2024)
Despite widespread, scientifically supported recognition of the scope of the climate crisis, and policies in place connecting sport to sustainable development, there remain concerns that the environment and climate change are rarely acknowledged within SDP activity and that even when they are, it is unclear how such policies are implemented, and to what effect. This raises the question of how and why the climate crisis and the attendant relationships between sport and sustainable development are understood and operationalized (or not) by stakeholders within the SDP sector. In this paper, therefore, we explore various perspectives and tensions around the environment and climate crisis within the SDP sector. To do so, we draw on interviews with SDP policy-makers (primarily from the United Nations and the International Olympic Committee) and SDP practitioners living and working in the global South in order to gauge the place of the environment and climate change in their everyday SDP policy-making, programming and practices. Overall, the data shows that while SDP stakeholders recognize the urgency of the climate crisis, the need for action, and the policy agenda linking sport to sustainable development, significant barriers, tensions and politics are still in place that prevent consistent climate action within SDP. Policy commitments and coherence are therefore needed in order to make climate action a core feature of SDP activity and practice.